2014
DOI: 10.5606/kbbihtisas.2014.45143
|View full text |Cite
|
Sign up to set email alerts
|

A new transcutaneous bone anchored hearing device - the Baha® Attract System: the first experience in Turkey

Abstract: Our study results suggest that the new bone conduction implant is promising for the patients with conductive or mixed hearing loss who are unable to wear conventional air conduction hearing aid and comparable to percutaneous systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 9 publications
3
31
2
1
Order By: Relevance
“…Devices which use bone conduction have been implanted with success for many years and percutaneous BAHA implants are accepted as the gold standard [2]. Their efficacy is well proved but unfortunately they have some important disadvantages effected by percutaneous abutment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Devices which use bone conduction have been implanted with success for many years and percutaneous BAHA implants are accepted as the gold standard [2]. Their efficacy is well proved but unfortunately they have some important disadvantages effected by percutaneous abutment.…”
Section: Discussionmentioning
confidence: 99%
“…However, such magnetic systems can cause different problems like limited transmission of vibrations through the skin, especially at high frequencies, and problems with good retention. Proper construction of systems which allow limitation of pressure on soft tissue, and development of modern processor technology which makes it possible to compensate for skin attenuation by increasing the amplification in affected frequencies seems to be crucial to prevent these problems [2, 10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pad of soft material lines the external magnet and distributes the pressure across the skin surface. Research has shown that the combination of advanced sound processing, stable single-point fixation in the bone, and even contact pressure results in efficient sound transmission (16,17) and minimal skin complications (17).…”
mentioning
confidence: 99%
“…Audiológiai eredményeink kiemelkedően jó rehabilitációs hatékony-ságról adtak tanúbizonyságot. Az általunk elért 51,58 ± 11,22 SD dBHL hallásteljesítmény, valamint 43,3 ± 16,02 SD dB beszédhallásküszöb átlagos javulása megegyezik a nemzetközi irodalomban fellelhető adatokkal [17,18]. A csonthoz horgonyzott hallásjavító implantátum-rendszerek gyermekkori alkalmazásának feltétele a betöl-tött minimum ötéves életkor és/vagy a 3 millimétert meghaladó koponyacsont-vastagság.…”
Section: Megbeszélésunclassified